BUNDA: KISAH CINTA 2 KODI BY ASMA NADIA: A STRUCTURALISM STUDY - Suhailee, Suhailee; Imron, Ali; Hasyim, Nafron; Sabardila, Atiqa; Markhamah, Markhamah (Lire Journal (Journal of Linguistics and Literature), 2020)
This study aims to describe the socio-historic background of (1) Asma Nadia and (2) the structure of Bunda: Kisah Cinta 2 Kodi, This study uses the descriptive qualitative method. The research strategy is embedded in case studies. The research data are in the form of words, phrases, sentences, and paragraphs in the novel Bunda: Kisah Cinta 2 Kodi that contains information about the socio-historic background of Asma Nadia, and the structure of the novel. The primary data source is the novel and the secondary data source is relevant journal articles. The data were collected through the library, observation, and documentation techniques. The data were analyzed using the semiotic reading method, namely heuristic and hermeneutic reading. The results of the study are (1) Sociohistorical setting: Asma Nadia was born into a literary family (her grandfather, Teuku Muhammad Usman El Muhammady and her two siblings, Helvy Tiana Rosa and her brother Aeron Tomino, and her husband, Isa Alamsyah, were writers). Her works have particular characteristics: Islamic theme, simple language, and the struggle of Moslem women. (2) The structure of the novel: the theme is the struggle of a mother in a family. It uses the flashback method since the story takes a regressive plot. The important figures are Kartika, Aryani, Farid, Bagja, Farid’s mother, Anton’s mother and Siti. The setting: schools, Kartika boarding house, campus canteens, cinemas, bookstores, Aryani's house, hospitals, abortion clinics, Tanah Abang market, Aryani's in-law's house, mushalla, and food stalls. Time setting: 1962, 1963, 1965, 1989, 1992, 1998 and 2000. Social setting: Kartika comes from Javanese and Minangkabau parents, whose works are civil servants and teachers.